Alexander y el dia terrible, horrible, espantoso, horroroso - Viorst, Judith ([Somers, N.Y.] : Live Oak Media, 1991)
On a day when everything goes wrong for him, Alexander is consoled by the thought that other people have bad days too.
Translation of: Alexander and the terrible, horrible, no good, very bad day.
Based on the book of the same title published: New York : AladdinBooks, 1989.
Side A has turn-the-page signals ; side B has uninterrupted reading.
Keywords: Children -- Attitudes -- Juvenile fiction -- Sound recordings